Correction: In vivo 808 nm image-guided photodynamic therapy based on an upconversion theranostic nanoplatform. Issue 33 (4th August 2016) - Liu, Xiaomin; Que, Ivo; Kong, Xianggui; Zhang, Youlin; Tu, Langping; Chang, Yulei; Wang, Tong Tong; Chan, Alan; Löwik, Clemens W. G. M.; Zhang, Hong
Abstract : Correction for ' In vivo 808 nm image-guided photodynamic therapy based on an upconversion theranostic nanoplatform' by Xiaomin Liu, et al., Nanoscale, 2015, 7, 14914–14923.